IPA 1968-1989: Fidelity and ecclesial sign - Vega-Centeno Bocángel, Imelda (1989)
Church memory remembers 1968 as the year of the Second General Conference of CELAM in Medellín. The ecclesial reflection reflected in the Medellin documents sought to translate the "aggiornamento" of the Second Vatican Council into the Latin American reality, allowing its renewing sap to vivify the Church of the continent. The prophetic word of the Church moved the consciences of men of good will, with a cry for peace that is the fruit of justice.